Determination of arsenic in peat samples using HG-AFS and L-cysteine as pre-reductant - Frank, Jutta; Krachler, Michael; Shotyk, William (Journal of analytical atomic spectrometry, 2006)
An accurate, sensitive, and robust analytical procedure for the direct determination of arsenic (As) in nitric acid digests of peat samples using hydride generation-atomic fluorescence spectrometry (HG-AFS) has been developed. Existing HG-AFS procedures developed for other environmental matrices employing potassium iodide (KI) as pre-reductant cannot be applied for the determination of As in peat samples, because they largely underestimate the actual As concentration. Here, the pre-reduction capabilities of KI and L-cysteine in nitric acid digests of peat and plant samples were tested systematically, revealing that only L-cysteine (12.8 g l−1) provided accurate results for peat samples. The newly developed analytical procedure was successfully applied to the determination of As in several peat samples and peat reference materials with concentrations ranging from ∼100 ng g−1 to ∼10000 ng g−1, as well as certified environmental reference materials yielding good agreement between found and certified values. The LOD of 4 ng l−1 and the precision of <3% for peat samples allowed the reliable quantification of As in all investigated peat samples. Results for As in selected peat samples obtained using the new HG-AFS procedure were confirmed in-house using ICP-SF-MS and HG-AAS.
First published as an advance article on the web 22nd December 2005
Gesehen am 29.09.2020